Strengthening Legislatures : Implications from Industrial Countries - Messick, Richard E. (World Bank, Washington, DC, 2012)
With more developing and post-communist states embracing democracy, improving the performance of their congresses, parliaments, and other legislative assemblies has become a must. These bodies make laws, hold the executive branch accountable, and represent citizen interests. Good governance demands that each of these tasks be done well. Thus aid agencies have begun supporting programs that train legislators and their staff, provide computers and buildings, and otherwise strengthen the legislative branch of government. But while some programs have succeeded, the overall results have been disappointing. One reason is that many programs have ignored a key principle of public sector reform: success requires changing the incentives facing public officials (World Bank 2000). More effective legislative aid programs will require donors to understand what motivates legislators and how those incentives can be altered. This note surveys the main factors shaping incentives for legislators in industrial countries and suggests how these factors can inform legislative reform in developing and transition economies.